As unidades municipais de cadastro do INCRA como apoio à regularização fundiária: uma proposta para os agricultores familiares do Vale do Ribeira/PR - Silva, João Wagner Gomes da (2019)
The need to make improvements in land regularization processes in Brazil in order to bring legal certainty to farmers, especially family members who do not have the full land ownership document, require actions to improve the implemented programs. Given the lack of regularity of their rural property, the squatter may, as a rule, have difficulty accessing public policies for rural credit, directly impacting the generation of family income. Thus, this research aims to develop a less restrictive and continuous flow proposal in the permanent support for opening land regularization processes in addition to the model currently implemented by the State of Paraná, which can be represented by INCRA’s Municipal Registered Units. In the City Halls. The research had a documentary exploratory methodological approach with a bibliographical review of the literature and legislation that were established in the land regularization process in Brazil and Paraná State, as well as a field research with the application of a questionnaire directed to agents. With a qualitative approach in order to identify how the actions and relationships of the agencies responsible for the implementation of the land regularization policy in the State of Paraná occur and the participation of the municipalities in the process. The survey results indicate the possibility of a new flow in land regularization as part of improvements to the Land Governance processes, representing an accessible, fast and less restrictive access road for rural landowners to request the regularization of their properties and an option. Institutional support for public agents managing this policy in the State.